A fuzzy-based mechanism for delay window adjustment to improve TCP performance in wireless multi-hop networks. (2017) - Nassiri, Mohammad; Mehdizadeh, Mojtaba
TCP protocol was initially designed for wired networks to guarantee reliable data transfer. In wired networks, TCP assumes congestion if data packets are dropped. However, this assumption does not hold when the end-to-end path includes wireless links, where, high bit error rate (BER), shared medium and dynamic nature of the wireless channel may cause packet loss. This results in a severe degrade in performance of standard TCP in wireless networks. On the other hand, TCP cannot be changed fundamentally due to the large base of installation in the wired network. Delayed-ACK generation at the TCP receiver has been proposed to mitigate collision rate within wireless network. However, choosing appropriate delayed window size is an important issue. In this article, we propose a new delayed-ACK approach based on a fuzzy controller to improve TCP performance in wireless networks. The major advantage of our mechanism is reducing the overhead and the collision rate in multi-hop wireless networks. We also compare our proposal with some of well-known studies. Simulations results confirm good performance of our mechanism.